Institutional Capacity Improvement Training Supports the Management of GLNP in Climate Change Mitigation - Rahmawaty; Rauf, Abdul; Harahap, R. Hamdani; Aththorick, T. Alief; Ismail, Mohd Hasmadi; Tedong, Peter Aning; Fujiwara, Takahiro; Harahap, Darmadi Erwin; Fitra Syawal Harahap; Masrizal Saraan; Ridahati Rambey; Ade Fitria; Wini Dirgahayu (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Gunung Leuser National Park (GLNP) is one of Indonesia's most important conservation areas. Around GLNP, there are a group manages bamboo forests in Pamah Simelir Hamlet. This activity aims to carry out outreach activities to increase the institutional capacity of sustainable bamboo communities to support the management of GLNP buffer areas in mitigating climate change. The activity methods include lecture methods, group discussions, brainstorming, role-playing, collective problem-solving, questionnaires and interviews with groups, and Focus Group Discussions (FGD). The results of the training activities showed that the group's technical skills had improved, especially in managing bamboo forests as part of conservation and climate change mitigation efforts. They can apply the techniques taught, such as planting and maintaining bamboo in a sustainable manner, as well as using bamboo as a raw material with economic value. Increasing these skills can reduce pressure on forest areas and improve the welfare of local communities. The training carried out has succeeded in positively boosting the institutional capacity of the Bambu Lestari Community, both in technical, managerial, and collaboration aspects. This activity can become a reference for local governments and stakeholders in adopting an inclusive and sustainability-oriented approach while involving local communities as partners in preserving the environment and facing the challenges of climate change.